Distribution patterns of influenza virus receptors and viral attachment patterns in the respiratory and intestinal tracts of seven avian species - Costa, Taiana (BioMed Central, 2012)
This study assessed the presence of sialic acid α-2,3 and α-2,6 linked glycan receptors in seven avian species. The respiratory and intestinal tracts of the chicken, common quail, red-legged partridge, turkey, golden pheasant, ostrich, and mallard were tested by means of lectin histochemistry, using the lectins Maackia amurensis agglutinin II and Sambucus nigra agglutinin, which show affinity for α-2,3 and α-2,6 receptors, respectively. Additionally, the pattern of virus attachment (PVA) was evaluated with virus histochemistry, using an avian-origin H4N5 virus and a human-origin seasonal H1N1 virus. There was a great variation of receptor distribution among the tissues and avian species studied. Both α-2,3 and α-2,6 receptors were present in the respiratory and intestinal tracts of the chicken, common quail, red-legged partridge, turkey, and golden pheasant. In ostriches, the expression of the receptor was basically restricted to α-2,3 in both the respiratory and intestinal tracts and in mallards the α-2,6 receptors were absent from the intestinal tract. The results obtained with the lectin histochemistry were, in general, in agreement with the PVA. The differential expression and distribution of α-2,3 and α-2,6 receptors among various avian species might reflect a potentially decisive factor in the emergence of new viral strains.